2005
DOI: 10.1128/aac.49.1.441-443.2005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of CTX-M-15-Producing Enterobacteria in Cameroon and Characterization of a bla CTX-M-15 -Carrying Element

Abstract: CTX-M-15-producing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…However, some of our isolates were moderately resistant to ceftazidime; this is in agreement with studies that described CTX-M-15-producing isolates susceptible or moderately resistant to ceftazidime [19,20]. Resistance to aminoglycosides (gentamicin, tobramycin and netilmicin), ciprofloxacin and trimethoprim/ sulfamethoxazole was observed in all the isolates and transconjugant analysis showed the co-transfer of these resistances with CTX-M-15.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, some of our isolates were moderately resistant to ceftazidime; this is in agreement with studies that described CTX-M-15-producing isolates susceptible or moderately resistant to ceftazidime [19,20]. Resistance to aminoglycosides (gentamicin, tobramycin and netilmicin), ciprofloxacin and trimethoprim/ sulfamethoxazole was observed in all the isolates and transconjugant analysis showed the co-transfer of these resistances with CTX-M-15.…”
Section: Discussionsupporting
confidence: 77%
“…Resistance to aminoglycosides (gentamicin, tobramycin and netilmicin), ciprofloxacin and trimethoprim/ sulfamethoxazole was observed in all the isolates and transconjugant analysis showed the co-transfer of these resistances with CTX-M-15. The close association of ESBL production with these resistances has been previously reported [7,19,21].…”
Section: Discussionmentioning
confidence: 95%
“…Since then, outbreaks of CTX-M-15 E. coli producers have been described in France, the United Kingdom, and Canada (2,15,32). In some studies, the simultaneous presence of OXA-30 was also reported (7).…”
Section: Discussionmentioning
confidence: 99%
“…Here we demonstrate the presence of bla CTX-M-15 within two different genetic environments in the same geographical region. The bla CTX-M-15 gene was directly linked to an upstream insertion sequence ISEcp1-like element (clusters I, III, and IV of the present study), as described in Canada, Cameroon, and India (2,7,13). In other isolates (eight strains of cluster II of the present study), an IS26 element was inserted within ISEcp1-like element preceding the bla CTX-M-15 gene, as described for epidemic strain A in the United Kingdom (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Cameroon showed high levels of resistance of commonly used antibiotics (penicillin, trimethoprim/sulfamethoxazole) in Gram negative bacilli and highlighted the emergence of multidrugresistant bacteria which produce extended spectrum beta-lactamases [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%